1999
DOI: 10.1021/ed076p1086
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Chemical Education in Russia: How to Attract the Young Generation to Chemistry under Conditions of "Chemophobia"

Abstract: Preparation of young people in special chemical groups at the Department of Chemistry of the Moscow State University is described. Actual problems of chemical education in Russia are discussed from the viewpoint of attracting promising young people to the chemical institutions of the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The negative anxiety has considerable significance in learning and achievement situations. The psychological studies illustrate the significance of anxiety in both learning and performance situations (Berdonosov et al, 1999;Black & Deci, 2000;Eddy, 2000;Möller, 1996). Jerusalem and Pekrun (1999) showed that negative anxiety was frequently related to learning and performance situations.…”
Section: Discussionmentioning
confidence: 99%
“…The negative anxiety has considerable significance in learning and achievement situations. The psychological studies illustrate the significance of anxiety in both learning and performance situations (Berdonosov et al, 1999;Black & Deci, 2000;Eddy, 2000;Möller, 1996). Jerusalem and Pekrun (1999) showed that negative anxiety was frequently related to learning and performance situations.…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of determining the level of anxiety towards science and mathematics education a limited number of assessment tools have been developed (Alvaro, 1978;Bowen, 1999;Hermes, 1985;Mallow, 1994;Richardon & Suinn, 1972;Spielberger et al, 1970;Udo et al, 2001). Results of the studies, in which these assessment tools were used, revealed that there was anxiety among the students (Berdonosov et al, 1999;Black & Deci, 2000;Chiarelott & Czerniak, 1987;Eddy, 2000), and the relationship between the students' anxiety levels towards courses and attitudes affected the students' achievement. Mallow and Greenburg (1982) stated that "there was a science anxiety among students, whereas it was less understood and rarely addressed case".…”
Section: Development Of a Scale Tomentioning
confidence: 99%
“…Anxiety feeling causes loss of helplessness, tension, panic, fear, inability to cope and concentration problem (Seligman Walkman et al, 2001). In addition, some studies showed that there was a negative relationship between anxiety and students' success because of anxiety in education (Berdonosov et al, 1999;Black & Deci, 2000;Eddy, 2000).…”
Section: Introductionmentioning
confidence: 99%